Obesity and place: Chronic disease in the 500 largest U.S. cities. Issue 5 (September 2018) - Fitzpatrick, Kevin M.; Shi, Xuan; Willis, Don; Niemeier, Jill
Abstract: Objectives: Extant research clearly points to a correlation between place and health, specifically as it pertains to chronic diseases like obesity. The present study examines this relationship among a diverse set of compositional place indicators and obesity rates across census tracts in the 500 largest cities in the United States. Methods: Using data compiled from the Robert Wood Johnson Foundation 500 Cities project and the Census' American Community Survey, the analyses examined aggregate relationships between sociodemographic, socioeconomic, and housing characteristics of census tracts and crude prevalence obesity rates in over 27, 000 census tracts located in the 500 largest cities in the United States. Results: Multivariate analysis confirms the place-chronic health connection. Regardless of variable groups, deteriorating places with higher concentrations of low-income, minority populations reported more obesity prevalence. Conclusions: Place matters. The continuing burden of zip code in the United States for disenfranchised populations will likely continue to force policymakers to examine the role that place-based prevention and place-focused medical care plays in the future health and well-being of U.S. residents.